Effects of cost sharing on long-term care service utilization among home-dwelling older adults in Japan. Issue 12 (December 2022) - Sano, Kazuaki; Miyawaki, Atsushi; Abe, Kazuhiro; Jin, Xueying; Watanabe, Taeko; Tamiya, Nanako; Kobayashi, Yasuki
Highlights: In 2015, Japan reformed the long-term care (LTC) insurance system. The policy change raised coinsurance rates only for higher-income people. We analyzed nationwide LTC claims data, covering most Japanese older adults. We demonstrated the policy change decreased LTC service use slightly. Slight service use reductions were observed across four main service subcategories. Abstract: Objectives: This study aimed to examine the effect of increased cost sharing on long-term care (LTC) service utilization among home-dwelling older adults, using nationwide long-term care insurance (LTCI) claims data in Japan. Methods: In August 2015, the coinsurance rate for Japanese LTCI increased from 10% to 20% for higher-income beneficiaries. We analyzed 27, 911, 076 person-month observations between April 2015 and July 2016 from 1, 983, 163 home-dwelling older adults (aged ≥ 65 years). We employed a difference-in-differences approach to estimate the effect of the increased coinsurance rate on overall LTC service utilization and for each of the four main service subcategories. The control group comprised those whose coinsurance rates remained at 10%. Results: The treatment group, whose coinsurance rate increased, accounted for 9.6% of all participants. The raised coinsurance rate caused statistically significant reductions of 0.46% (95% confidence interval [CI]: 0.36%, 0.56%) and $25.7 (95% CI: $23.7, $27.8) in the percentage of utilization of LTC services and total monthly LTC expenditures per person, respectively. Service utilization decreased in each of the four service subcategories. Conclusions: The increased coinsurance rate resulted in statistically significant but small reductions in LTC service utilization overall and in each service type among higher-income home-dwelling beneficiaries. Requiring more cost sharing from higher-income individuals may alleviate the fiscal burden on LTC systems without serious reductions in service utilization.